Person-Centered-Care Climate in a Tertiary Hospital: Staff Perspective - Al-Surimi K; Alhayek Z; Edvardsson D; Al-Khateeb B; Shaheen N (Dove Medical Press, 2021)
Khaled Al-Surimi,1- 3 Zahra Alhayek,1,2 David Edvardsson,4 Badr Al-Khateeb,1,2 Naila Shaheen1,5 1King Saud bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Kingdom of Saudi Arabia; 3Faculty of Medicine and Health Sciences, Thamar University, Dhamar, Yemen; 4Department of Nursing, Umea University, Umea, Sweden; 5Department of Biostatistics and Bioinformatics, King Abdullah International Medical Research Center, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Naila Shaheen Email drnaila@hotmail.comIntroduction: Most health care systems strive to improve the quality, safety and value of healthcare, with an emphasis on moving towards patient-centered care/person-centered care (PCC) approach. The aim of the current study was to assess health care providers' perspectives on PCC climate in hospital setting and to identify the role of providers in determining the perception of the PCC climate.Methods: A survey, using person-centered climate questionnaire-staff version, was employed in health care providers of a tertiary care hospital. Data included variables age, gender, education level, occupation, and years of experience and three PCC dimensions. PCC overall and subscale scores were reported as mean and standard deviation. Factors associated with PCC climate perception were analyzed using a Poisson model.Results: Out of 1216 respondents; the majority 47% aged between 18 and 34 years; 79% women, 68% were nurses. The overall mean score was 45.96± 15.36 (range 0- 70). Subscale scores were Safety 20.15± 5.0 (range 0- 30), Everydayness 12.02± 3.52 (range 0- 20) and Community 13.79± 3.34 (range 0- 20). Increasing age was a significant factor associated with PCC scores for the overall, safety, everydayness, and community scales, with a positive association. Lower scores were reported more by women compared with men, for overall (p=0.0005), and everydayness (p=0.006) scales. Higher safety scores were reported by health care providers with a diploma compared to master's degree (p=0.009), Ph.D. (p=0.007), for technicians compared with nurses (p=0.007), and for day shift compared with day/night shift workers (p=0.025). PCC scores were not significantly different across health care providers' years of experience.Conclusion: There is a room for PCC climate improvement based on the low scores compared to the literature. The study findings indicated that the main factors associated with HCPs' perception of PCC were higher age and female gender, and these factors would benefit from further research.Keywords: health care providers' perception, person-centered care, psychosocial climate, tertiary care facility, work climate